دور القياس والإفصاح المحاسبي عن التكاليف البيئية في تعزيز جودة المعلومات المحاسبية - حفاصة, أمينة; فرحات, عباس (جامعة الوادي - University of Eloued, 2017)
اهتمت هذه الورقة البحثية بتسليط الضوء على دور القياس والإفصاح المحاسبي للتكاليف البيئية في تعزيز جودة المعلومات المحاسبية، ومن أجل نزع الغموض حول متغيرات الدراسة تم التطرق للإطار النظري لمحاسبة التكاليف البيئية وعرض مختلف طرق ومداخل قياس التكاليف البيئية وكذا محددات الإفصاح عنها في القوائم المالية.كما تم تحديد معايير قياس جودة المعلومات المحاسبية والخصائص النوعية الرئيسية منها والثانوية. توصلت الدراسة إلى مجموعة من النتائج والتي كان أبرزها أن الإفصاح عن التكاليف البيئية وتحديدها بدقة يؤدي إلى سهولة تخصيصها وتحميلها على المنتج بشكل صحيح، وبالتالي الحصول على معلومات محاسبية ذات جودة ومفيدة لمستخدميها في اتخاذ القرارات المناسبة The purpose of this paper was to highlight the role of accounting measurement and accounting for environmental costs in enhancing the quality of accounting information. In order to demystify the variables of the study, the theoretical framework of environmental cost accounting was presented. It also presented the various methods and means of measuring environmental costs as well as the determinants of disclosure in the financial statements. Define the criteria for measuring the quality of the accounting information and its main and secondary qualitative characteristics. The results of the study were summarized as follows: The disclosure of environmental costs and their precise identification leads to easy allocation and loading on the product properly, thus obtaining accounting information of quality and useful to its users in making the appropriate decisions
The role of accounting measurement and disclosure on environmental costs in enhancing the quality of accounting information
مقال بمجلة الدراسات المالية والمحاسبية . مج 08 ع01. جوان 2017 . جامعة الوادي
Keywords: التكاليف البيئية، جودة المعلومة المحاسبية، الإفصاح البيئي، القياس المحاسبي; environmental costs, quality of accounting information, environmental disclosure, accounting measurement.